A parametric BIM approach to foster bridge project design and analysis - Girardet, Alexis; Boton, Conrad (Automation in construction, 2021)
Advancements in technology have contributed significantly to building information modeling (BIM)-based construction project management. However, the BIM approach was developed mainly around building construction projects and few efforts have been devoted to projects related to infrastructures such as bridges. For such projects, there are often significant geometric and semantic variations between structures, making it difficult to use existing BIM data schemas. Recent works indicate that parametric modeling could represent a solution providing greater design efficiency and interoperability, but the literature on the subject remains extremely sparse. The objective of the present study is to develop a parametric file that is able to generate all types of bridges from a single parametric file. The file developed uses a parametric algorithm for modeling bridge elements in a design software application and for generation and analysis of the model in a structural analysis software application. •The article proposes a parametric BIM approach to foster bridge project design and analysis.•The file developed uses a parametric algorithm for modeling bridge elements in a design software application.•It allows the generation and analysis of a 3D model of the bridge in a structural analysis software application.•The solution is validated through its application to real projects.•The study offers a practical and innovative solution for bridge modeling, which can be used for various types of projects.